2020
DOI: 10.1111/bph.14925
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin accelerates the revascularization of transplanted pancreatic islets

Abstract: Background and Purpose Pancreatic islet transplantation is a promising therapeutic approach for Type 1 diabetes. A major prerequisite for the survival of grafted islets is a rapid revascularization after transplantation. Erythropoietin (EPO), the primary regulator of erythropoiesis, has been shown to promote angiogenesis. Therefore, we investigated in this study whether EPO improves the revascularization of transplanted islets. Experimental Approach Islets from FVB/N mice were transplanted into dorsal skinfold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Unfortunately, both the DPO low-dose and the DPO high-dose treatment failed to accelerate the process of revascularization, as indicated by a similar functional capillary density between the 3 experimental groups throughout the observation period. In fact, the DPO low-dose treatment showed an even lower angiogenic response when compared to the EPO treatment performed in our previous study [ 30 ]. Furthermore, the relative size of the vascular network and the endocrine revascularization did not differ between the three experimental groups.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Unfortunately, both the DPO low-dose and the DPO high-dose treatment failed to accelerate the process of revascularization, as indicated by a similar functional capillary density between the 3 experimental groups throughout the observation period. In fact, the DPO low-dose treatment showed an even lower angiogenic response when compared to the EPO treatment performed in our previous study [ 30 ]. Furthermore, the relative size of the vascular network and the endocrine revascularization did not differ between the three experimental groups.…”
Section: Discussionmentioning
confidence: 54%
“…We have recently shown that EPO is a promising compound to accelerate the revascularization process of transplanted pancreatic islets. However, the pro-angiogenic effect was predominant, when EPO was administrated prior islet transplantation [ 30 ]. This pretreatment might not be possible to transfer in a clinical setting, as the transplantation process is a swift procedure with little time between receiving the donor organ and the transplantation itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice with a non‐fasting blood glucose level ≥ 350 mg/dl served as recipients for islet transplantation (Sakata et al , 2012). Four hundred FI, 300 FI, 250 FI, 200 FI, and 250 PI + MVF were injected under the kidney capsule of diabetic mice using a 10 µl Hamilton syringe, as described previously in detail (Menger et al , 2020). Blood glucose levels and body weight were monitored over the entire observation period of 28 days twice a week.…”
Section: Methodsmentioning
confidence: 99%
“…Significant research efforts have been conducted to promote the revascularization and, thus, to improve nutrient and oxygen supply of grafted islets during the first post‐transplantational days (Song et al , 2019; Menger et al , 2020). A promising strategy to achieve this is the prevascularization of the transplantation site, as already described for subcutaneous tissue by means of a catheter technique (Pepper et al , 2015).…”
Section: Introductionmentioning
confidence: 99%